2001
DOI: 10.1016/s0029-7844(00)01173-x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal DNA in maternal circulation of first-trimester spontaneous abortions

Abstract: Fetal DNA is present in the maternal circulation of first-trimester spontaneous abortions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…In the present study, we also found that cell-free fetal DNA and cell-free total DNA levels were significantly increased in SA cases compared to controls. These results were consistent with those from previous studies [15], [16]. Additionally, we demonstrated that the use of cell-free fetal DNA and cell-free total DNA was more informative in predicting SA with fetal chromosomal aneuploidy than SA with fetal normal karyotype.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, we also found that cell-free fetal DNA and cell-free total DNA levels were significantly increased in SA cases compared to controls. These results were consistent with those from previous studies [15], [16]. Additionally, we demonstrated that the use of cell-free fetal DNA and cell-free total DNA was more informative in predicting SA with fetal chromosomal aneuploidy than SA with fetal normal karyotype.…”
Section: Discussionsupporting
confidence: 92%
“…Prior studies have reported that an increase in cell-free total DNA, as well as cell-free fetal DNA, is associated with SA [15], [16]. This increase in cell-free total DNA may be induced by the release of circulating factors into maternal circulation, which can result in damage to maternal vascular endothelial cells and multi-system dysfunction [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations